Obscenity, Morality, and the First Amendment: the First LGBT Rights Cases Before the Supreme Court - Ball, Carlos A. (Columbia Journal of Gender and Law, 2014)
The Supreme Court decided its first two cases involving LGBT litigants in 1958 and 1962, respectively. Surprisingly, commentators have paid little attention to these early cases despite the fact that the Court in both instances sided with the publishers of gay magazines in the face of the government s claim that the publications were obscene. This Article fills this gap in the literature by exploring how the challengers prevailed before the Supreme Court at a time when the vast majority ofAmericans strongly disapproved of same-sex sexual relationships and conduct. The Article contends that the best way of understanding the cases is to view them as part of the push by mid-twentieth century courts to "demoralize" the law of obscenity, that is to reject, minimize, or ignore the government Scontention that obscenity laws were needed to promote and protect public morality. The Article also explores the historical importance of the first LGBT rights victories before the Supreme Court, explaining how they contributed in important ways to the formation and strengthening of LGBT identities and communities during the early days of the LGBT rights movement. Finally, the Article analogizes between the demoralization of obscenity law under the First Amendment and the demoralization of substantive due process and equal protection law in matters of sexual orientation that resulted from the Court s later cases involving sodomy and marriage laws. In doing so, the Article explains how and why the demoralization offree speech law preceded the demoralization of other areas of constitutional law.